Decoding patterns of human brain activity.[article]. - Tong, Frank
Considerable information about mental states can be decoded from noninvasive measures of human brain activity. Analyses of brain activity patterns can reveal what a person is seeing, perceiving, attending to, or remembering. Moreover, multidimensional models can be used to investigate how the brain encodes complex visual scenes or abstract semantic information. Such feats of "brain reading" or "mind reading" though impressive, raise important conceptual, methodological and ethical issues. What does successful decoding reveal about the cognitive functions performed by a brain region? How should brain signals be spatially selected and mathematically combined to ensure that decoding reflects inherent computations of the brain rather than those performed by the decoder? We highlight recent advances and describe how multivoxel pattern analysis can provide a window into mind-brain relationships unprecedented specificity, when carefully applied. However, as brain-reading technology advances, issues of neurotics and mental privacy will be important to consider. - (from the authors)